Classifying Dental Caries Types Using Panoramic Dental Images Using Watershed Method and Multiclass Support Vector Machine - Putra, S.Pd., M.T., Rangga Pahlevi Putra; Rahman, Aviv Yuniar (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2023)
Teeth are one of the calcified and hard structures found in the human mouth. One of the tooth defects that often appears and is experienced by several people in the world is damage caused by dental caries. Diseases that can arise from dental caries include swelling of the gums and fever in the body. To classify and determine the level of damage in dental disease, dentists usually utilise examinations through dental panoramic images. Dental panoramic images are digital images of x-rays that can help provide a lot of information about teeth such as cavities or tooth structure. However, the problem that occurs sometimes to identify or classify the type of caries is still found to be a mismatch of analysis so that technological aids are needed to provide analysis or decision support. Therefore, by applying digital image processing technology by applying methods in image processing, namely Watershed segmentation and the Multiclass Support Vector Machine method, it is possible to classify the type of caries using dental panoramic images. From the results of the research conducted, it can be explained that the results of segmentation of dental panoramic images using the Watershed method can show the detected caries area spots. Meanwhile, the use of the Multiclass SVM method for the classification method shows accuracy results reaching 88%.